Sinapine thiocyanate exhibited anti-colorectal cancer effects by inhibiting KRT6A/S100A2 axis - Yan Yang; Zhirui Zeng; Lian Li; Shan Lei; Yingmin Wu; Tengxiang Chen; Jinjuan Zhang (Cancer Biology & Therapy, 2023)
Sinapine thiocyanate (ST), an alkaloid existed extensively in seeds of cruciferous plants, exhibits a number of pharmacological effects, including anti-inflammatory and anti-malignancy properties. However, it is still unknown what effects and molecular mechanisms ST has on colorectal cancer (CRC). In the current study, it was indicated that ST inhibited proliferation, colony formation, and apoptosis in vitro, as well as arrested the G1 phase of CRC cells. There was a significant repressive effects of ST on invasion and migration of CRC cells in vitro. RNA-sequencing indicated that 750 differentially expressed genes existed in CRC cells after ST treatment, and enrichment analysis demonstrated that ST obviously decreased the activation of keratinization pathways. Among DEGs enriched in keratinization, keratin 6A (KRT6A) was decreased the most significant, as well as its target gene S100 calcium-binding protein A2 (S100A2). Low expression of KRT6A and S100A2 signatures indicated a favorable prognosis in CRC patients. Moreover, we found overexpression of KRT6A relieved the inhibitory effects of ST in CRC cells. Furthermore, ST inhibited the CRC cell proliferation in vivo, and reduced KRT6A and KI67 expression in xenograft tumor. Taken together, we demonstrated that ST exhibited anti-CRC properties by inhibiting KRT6A/S100A2 axis. It is possible that ST can be used as a treatment for CRC.